ISOLASI BAKTERI Salmonella sp. PADA FESES ANAK AYAM BROILER DI PASAR ULEE KARENG BANDA ACEH (Isolation of Salmonella sp. in Feces of Broiler Chicks at Ulee Kareng Market Banda Aceh) - Afriyani Afriyani; Darmawi Darmawi; Fakhrurrazi Fakhrurrazi; Zakiah Heryawati Manaf; Mahdi Abrar; Winaruddin Winaruddin (Universitas Syiah Kuala, 2016)
The research aimed to isolate Salmonella sp.in feces of broiler chicks. Fifteen feces samples of broiler chick were obtained from Ulee Kareng Market in Banda Aceh. Chick cloaca was swabbed using a sterile cotton swab, put into the microtube, and brought to the Microbiology Laboratory of Veterinary Medicine Faculty, Syiah Kuala University. The samples were incubated in selenite cystine broth (SCB) medium, cultured in salmonella shigella agar (SSA) and separated colonies were inoculated in nutrien agar (NA) at 37° C for 24 hours. Bacteria stained with Gram staining then tested biochemically. The result showed that Salmonella sp. were identified in 9 out of 15 feces chicks samples. It ca be concluded that broiler chick in Ulee Kareng Market Banda Aceh contaminated with bacteria Salmonella sp.